A giant tonsillolith - Alfayez, Abdulrhman (Saudi Med J, 2018)
Tonsillar stones are the products of calcified accumulates of cellular debris and microorganisms, in the crypts of palatine tonsils. Tonsillar stones are common findings and the known cause of bad breath (halitosis). Development of large tonsillar stones, however, is rare with only a few cases reported in the literature. We present the case of a 45-year-old man with a history of recurrent sore throat and tonsillitis for a long period, and snoring with other unremarkable ears, nose and throat findings. A large-sized tonsillar stone detected in the left tonsil measured 3.1 × 2.3 cm. The patient underwent elective stone removal and tonsillectomy.